Predictors of Overweight and Obesity among Children in Haldwani, Uttarakhand - Choudhary, Bhawna; Singh, Nutan; Bathla, Ankush; Chand, Ramesh (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Obesity has become a concerning pediatric health problem in the modern era with lifestyle changes in globalization, economic development and easy access to technology. The aim of the study is to study the anthropometric profile of overweight and obesity and its associated risk factors. Subjects and Methods: A school-based cross-sectional study was implemented among randomly chosen 100 obese and overweight children aged between 10-18 years over 15 months. Data was collected using a structured self-administered questionnaire and anthropometry was done and categorized as overweight and obese as per WHO BMI- age cutoff. Results: 41 % (n=41) were obese and 59% (n=59) were overweight. 65 % (n=65) were males. In all the age groups the mean weight of males was more except in the age group 10-12 years. Mean weight (64.39 12.88 kg) and mean BMI (26.04 1.95 kg/m2) of obese children is significantly higher than mean weight (56.73 9.76 kg) and mean BMI (23.25 1.98 kg/m2) of overweight children respectively. Risk factors like skipping breakfast (p= 0.034), calorie excess (p= 0.032), junk food intake more than once (p=0.008) and junk food daily (p=0.036) were found to be significantly associated with childhood obesity. Conclusion: Sensitization of parents and teachers with school-based programs like active participation in sports, regular anthropometric examinations of students are important measures that can be taken to curb this rising problem.